Notch2 Signaling Maintains NSC Quiescence in the Murine Ventricular-Subventricular Zone - Anna Engler (Cell Reports, 2018)
Neurogenesis continues in the ventricular-subventricular zone (V-SVZ) of the adult forebrain from quiescent neural stem cells (NSCs). V-SVZ NSCs are a reservoir for new olfactory bulb (OB) neurons that migrate through the rostral migratory stream (RMS). To generate neurons, V-SVZ NSCs need to activate and enter the cell cycle. The mechanisms underlying NSC transition from quiescence to activity are poorly understood. We show that Notch2, but not Notch1, signaling conveys quiescence to V-SVZ NSCs by repressing cell-cycle-related genes and neurogenesis. Loss of Notch2 activates quiescent NSCs, which proliferate and generate new neurons of the OB lineage. Notch2 deficiency results in accelerated V-SVZ NSC exhaustion and an aging-like phenotype. Simultaneous loss of Notch1 and Notch2 resembled the total loss of Rbpj-mediated canonical Notch signaling; thus, Notch2 functions are not compensated in NSCs, and Notch2 is indispensable for the maintenance of NSC quiescence in the adult V-SVZ.